2014
DOI: 10.1016/j.foodhyd.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium ions and pH on the structure and rheology of carrot-derived suspensions

Abstract: Effect of calcium ions and pH on the structure and rheology of carrot-derived suspensionsMoelants, K.R.N.; Cardinaels, R.M.; Greef, de, K.; Daels, E.; Van Buggenhout, S.; Van Loey, A.M.; Moldenaers, P.; Hendrickx, M.E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In the case of LTB carrots, during incubation at 60°C, the endogenous PME demethylesterified the pectin, resulting in low DMs. Similar results were observed by Moelants et al (2014), in which carrot samples incubated at 60°C for 24 h showed a lower DM of pectin compared to those blanched at 95°C. On the other hand, high temperature blanching (of HTB samples) inactivated PME and resulted in an average high DM of pectin in the carrot tissue particles.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In the case of LTB carrots, during incubation at 60°C, the endogenous PME demethylesterified the pectin, resulting in low DMs. Similar results were observed by Moelants et al (2014), in which carrot samples incubated at 60°C for 24 h showed a lower DM of pectin compared to those blanched at 95°C. On the other hand, high temperature blanching (of HTB samples) inactivated PME and resulted in an average high DM of pectin in the carrot tissue particles.…”
Section: Resultssupporting
confidence: 88%
“…A sieve shaker (Retsch, Aartselaar, Belgium) equipped with a set of sieves with pores sizes of 40, 80, 125, 250, 500 and 1000 lm was used. Pulp obtained on each sieve was assembled and drained over a filter to remove excess water as described by Moelants et al (2014). The particles obtained were either used for the isolation of alcohol insoluble residue for further pectin characterization (see Section 2.4) or stored over 70% ethanol for at least two weeks before further use for microscopy examinations (see Section 2.7).…”
Section: Separation Of Carrot Purée Particles Based On Sizementioning
confidence: 99%
See 2 more Smart Citations
“…The nature of these interactions could be electrostatic, frictional or elastic, depending on the particular system [2]. Electrostatic interactions in the serum phase are common to occur either between protein-pectin [3,4] or pectin-pectin compounds [5]. It is not yet completely clear what is the relative effect of the particle and serum phases to the rheological properties of the whole suspension is [6].…”
Section: Introductionmentioning
confidence: 99%